Apports des essais mécaniques : Évaluation de la vulnérabilité et des risques de dégradation des peintures. - Alain Roche (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The conservation of paintings on canvas is closely associated with the understanding of their physico-mechanical properties. Using mechanical testing is essential when developing tools to assess the level of vulnerability and risks of mechanical degradation in paintings. This paper addresses a series of studies highlighting the need of a systemic approach to decision-making for structural treatments.